2017
DOI: 10.1177/1539449217730355
|View full text |Cite
|
Sign up to set email alerts
|

Analyzing State Autism Private Insurance Mandates for Allied Health Services: A Pilot Study

Abstract: Due to the prevalence, severity, and costs associated with autism spectrum disorders (ASDs), it has become a public health issue. In response, state governments have adopted ASD-specific private insurance mandates requiring coverage of ASD screening, diagnosis, and treatment. Despite rapid uptake of these laws, differences exist in the type and levels of coverage, especially for allied health services including occupational therapy. We piloted a structured legal research methodology to code ASD insurance manda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 21 publications
0
9
0
Order By: Relevance
“…As previously mentioned, one possible benefit of receiving a clinical diagnosis is to facilitate access to appropriate services. Over the past decade, many states have enacted laws that mandate insurance companies to reimburse evidence‐based treatments for ASD; including but not limited to behavioral therapy (e.g., applied behavior analysis), occupational therapy, physical therapy, speech therapy, social skills training, and a combination of these [Barry et al, ; Dawson & Burner, ; Douglas, Benevides, & Carretta, ; Kasari, ; Zwaigenbaum et al, ]. However, justification for the medical necessity of therapies is most often needed before insurers will approve and reimburse service requests.…”
Section: Discussionmentioning
confidence: 99%
“…As previously mentioned, one possible benefit of receiving a clinical diagnosis is to facilitate access to appropriate services. Over the past decade, many states have enacted laws that mandate insurance companies to reimburse evidence‐based treatments for ASD; including but not limited to behavioral therapy (e.g., applied behavior analysis), occupational therapy, physical therapy, speech therapy, social skills training, and a combination of these [Barry et al, ; Dawson & Burner, ; Douglas, Benevides, & Carretta, ; Kasari, ; Zwaigenbaum et al, ]. However, justification for the medical necessity of therapies is most often needed before insurers will approve and reimburse service requests.…”
Section: Discussionmentioning
confidence: 99%
“…Using administrative data, the second study found that children were more likely to be enrolled in the waiver program if they lived in census tracts characterized by a higher percentage of families with incomes $200% of the federal poverty level, a higher percentage of women ages 25 and older with at least a high school degree, and a higher percentage of residents who identify as "white alone" (22). Given the substantial number of children diagnosed as having ASD, the promise of early intensive behavioral intervention, and the sizable investment made in ASD treatment (20,23,24), these findings highlight the need to investigate enrollment in Medicaidfunded early intensive behavioral intervention in other states. In this study, we examined equity in the enrollment of children with ASD in an early intensive behavioral intervention Medicaid waiver by answering the question, How do enrollees' neighborhood demographic characteristics compare with those of the general state population, after control for enrollees' age, sex, and race-ethnicity?…”
Section: Highlightsmentioning
confidence: 99%
“…Health services research examines how policies on health care access and insurance coverage influence disparities in populations. Douglas and colleagues (2017) used structured legal research methods to code autism spectrum disorder private insurance mandates from 14 states to identify more granular variables that could be used to better assess how the mandates might affect service provision and outcomes. Their preliminary data on allied health services demonstrated that the methodology was reliable and could detect differences between states in multiple aspects of the mandates.…”
Section: Health Inequities and Health Disparitiesmentioning
confidence: 99%
“…There are a growing number of occupational therapy resources and tools designed for practitioners who want to add health surveillance methods and community-centered approaches to their practice (Hyett, McKinstry, Kenny, & Dickson-Swift, 2016). This special issue on occupational therapy and public health highlights research that demonstrates the occupational therapy lens in health surveillance (Hand et al, 2017; Peachey, Wenos, & Baller, 2017), community-centered programs (Coker-Bolt et al, 2017; Hyett, Kenny, & Dickson-Swift, 2017), and health disparities or inequities (Barnekow et al, 2017; Douglas, Benevides, & Carretta, 2017; Williamson, Conteras, Rodriquez, Smith, & Perkins, 2017).…”
mentioning
confidence: 99%